Vibration simulation of plate with attached multiple absorbers - Mohamad Nasir, Nadia Nurnajihah (2014)
In general, solutions for standards to improve the vibration and noise problems is to redesign or modify the system such as increasing the thickness of the wall panels, enhancing the elasticity of the structure, and increase the damping mechanism of the structure. So in this study, the concept of Dynamic Vibration Absorbers (DVA) are used to reduce vibration or amplitude. On a Simply Supported Plate (SSP) structure, the method used in this study were of analytical equations and ﬁnite element analysis. MATLAB ® is used to solve the equations of analytical theory, as well as simulation results verify the ANSYS ®. The study found that the analytical and simulation equation for SSP are same. The frequency range used are 10 Hz to 500 Hz and there are a number of modes show. In addition, the mass and damping in the absorber is changed. It aims to identify the mass and damping are most suitable for use in absorber system. Once seen, the mass of 1.0 kg more suitable for use as a percentage reduction or vibration amplitude is the highest of 40.99%. The damping values shows that the percentage reduction in the amplitude of the vibration or spring, 10 N / m is 44.64%. Further, this study was undertaken by placing the absorber at different locations conﬁguration. This was followed by the addition of a single absorber and multiple absorber to see the average percentage reduction in vibration or amplitude. Overall global reduction of the four absorber is 68.07% compared to the single absorber only 33.31% reduction. Finally, it can be concluded that multiple vibration absorber can reduce the overall global vibration compared to a single absorber. However, for structures that take into account the weight of the main things to consider increasing the number of absorbers as excessive weight of the structure will result in a reduction in vehicle fuel efﬁciency, aerospace, automotive and machine systems.